ANALISIS MUATAN SOAL LITERASI DALAM BUKU MATEMATIKA KURIKULUM MERDEKA KELAS X BERDASARKAN PISA - Wahyuni, Indah; Firnanda, Dwi Tri Fresti; Munawaroh, Lailatul (TRANSFORMASI, 2023)
This research was conducted to determine the percentage of literacy questions in the competency test in the Mathematics Textbook for Class X based on PISA. The research was conducted using qualitative methods based on PISA levels. The object of the research was a class X mathematics book. The results showed that the book contained 88% literacy questions, with 8% of the questions being at level 1 of PISA, 31% being at level 2, 29% being at level 3, 21% being at level 4, 8% being at level 5, and 3% being at level 6